POLA PERTUMBUHAN SAPI PERAH FRIESIAN HOLSTEIN BETINA DARI LAHIR SAMPAI UMUR KAWIN PERTAMA DI BPPIB-TSP BUNIKASIH - Suci Megawati; Didin Supriat Tasripin; Heni Indrijani (Jurnal Produksi Ternak Terapan, 2023)
Growth is a dynamic process, which is a reflection of changes in body structure due to genetic and environmental responses. The purpose of this study was to determine the growth curve and obtain the best curve model for Friesian Holstein female dairy cows in BPPIB-TSP Bunikasih. The research used local and imported FH dairy cows aged 0-18 months. The growth curve models used are the models Gompertz, Logistic, Polynomial and MMF (Morgan Mercer Flodin). The results obtained show that the growth curve model has a different level of accuracy. Polynomial model for local FH dairy cows has a standard error value of 2.1247 and a correlation coefficient value of 0.9997, while for imported FH dairy cows it has a standard error value of 3.5368 and a correlation coefficient value of 0.9993. The growth pattern of imported cattle is faster than that of local cattle.Keyword : Friesian-Holstein (FH), Females, Growth Curve, Local, Imported